IgG4‐related sclerosing cholangitis, a mimicker of the cholangiocarcinoma: A case report - Siddinath Gyawali; Biraj Pokhrel; Pratik Uprety; Arun Gnawali (Clinical Case Reports, 2023)
Abstract An 83‐year‐old‐male patient presented with obstructive jaundice, whose imagings were consistent with the cholangiocarcinoma of the distal common bile duct. The tumor markers were within normal limits. IgG4 level was raised; therefore, IgG4‐sclerosing cholangitis was made as the provisional diagnosis. Steroid therapy was started to which he responded well.